The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-6632.20150322s00003564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Arsenic and Manganese Removal From Water by Chlorine Oxidation Followed by Clarification

Abstract: -This paper investigates the simultaneous removal of arsenic [As(V) or As(III)] and manganese [Mn(II)] from natural waters of low and high turbidity by clarification (with polyaluminum chloride and aluminum sulfate as primary coagulants) associated or not with chlorine pre-oxidation. The results showed that the clarification process exhibited low Mn(II) removal, that varied from 6% to 18% and from 19% to 27% for natural waters of low and high turbidity, respectively. The use of chlorine as pre-oxidant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Conventionally, break-point chlorination [ 5 ], the stripping method, ion exchange [ 6 , 7 ], and biological methods [ 8 , 9 ] are used to get rid of NH 4 + -N; while pre-oxidation with strong oxidants combined with coagulation, precipitation, and filtration processes [ 10 ] are mainly used to remove Mn 2+ . However, for the raw water with NH 4 + -N and manganese coexisting, Huang and others found a new way to remove the two pollutants simultaneously in a previous study [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, break-point chlorination [ 5 ], the stripping method, ion exchange [ 6 , 7 ], and biological methods [ 8 , 9 ] are used to get rid of NH 4 + -N; while pre-oxidation with strong oxidants combined with coagulation, precipitation, and filtration processes [ 10 ] are mainly used to remove Mn 2+ . However, for the raw water with NH 4 + -N and manganese coexisting, Huang and others found a new way to remove the two pollutants simultaneously in a previous study [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although As and Mn have been removed separately or exclusively [7,8], their simultaneous adsorption has not been conducted to date. Two previous studies have reported the removal of As, Mn, and Fe [6,9] and one study developed a treatment system using coagulation and filtration for the simultaneous removal of As and Mn [10].…”
Section: Introductionmentioning
confidence: 99%
“…in wastewater could be decreased by coagulation with iron and aluminium salts; nevertheless, this has suffered from relatively low effectiveness and additional hazardous sludge to be treated (Ló pez-Muñ oz et al, 2017;Lata & Samadder, 2016). Pre-oxidation of As(III) to As(V) may facilitate the coagulation (Pires et al, 2015). Chlorine, sodium hypochlorite, chlorine dioxide, ozone, hydrogen peroxide, permanganate (or manganese dioxide) and Fenton's reagents were frequently used in the oxidation of As(III) in wastewater (Ebrahiem et al, 2017;Butnariu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%